EMPLOYEE PERFORMANCE AT PUSKESMAS CIKULUR, LEBAK REGENCY - Neneng Santi Purnawati; Triana Indrayani; Vivi Silawati (International Journal of Multidisciplinary Research and Literature, 2026)
This study examines the factors influencing employee performance at Puskesmas Cikulur, located in Lebak Regency, Indonesia. A quantitative approach was used, and a survey was conducted with 104 employees at Puskesmas to explore the impact of organisational culture, work discipline, and loyalty on employee performance. The findings show that 95.2% of employees reported a positive organisational culture, 96.2% indicated high work discipline, and 93.3% demonstrated high loyalty. Regression analysis revealed that organisational culture, work discipline, and loyalty had statistically significant positive effects on employee performance (p-values of 0.003, 0.002, and 0.004, respectively). However, competence and motivation did not significantly influence employee performance, with p-values of 0.329 and 0.465, respectively. These results suggest that enhancing organisational culture, improving work discipline, and fostering loyalty are key strategies for improving employee performance. This study provides important insights for healthcare management at Puskesmas, demonstrating that factors such as culture and discipline should be prioritised to improve overall employee performance, which is critical to delivering quality healthcare services in primary healthcare settings.